SINUPRET IN THE TREATMENT OF ACUTE PURULENT OTITIS MEDIA IN CHILDREN WITH CHRONIC ACTIVE HEPATITIS (Euro-Asia Conferences, 2021)
To date, otorhinolaryngologists do not have a single opinion on the treatment of acute purulent otitis media in children against the background of chronic active hepatitis. The proposed methods of conservative treatment by the authors in many cases do not give the desired effect. In this regard, this problem remains relevant, requires the search for new methods of treatment with the use of the latest generations of medicines